AN INNOVATIVE USE OF LARYNGEAL MASK AIRWAY IN PATIENTS UNDERGOING FOR NASAL SURGERY - Kumar, Dileep (Journal of Ayub Medical College Abbottabad, 2022)
Emergence from general anaesthesia after nasal surgery offers several challenges, especially if there is presence of blood and secretion in pharynx. This may provoke bucking, coughing and laryngospasm. Some of these patients may require high concentration of oxygen through the anaesthesia mask, however, this may be difficult due to presence of nasal packs and/or splints (1). Various methods have been advocated to overcome emergence challenges in these patients for example patient involvement by recalling mouth breathing at the time of extubation, avoidance of nasal splints and packing and allowing deep endotracheal tube extubation (2). Nevertheless, post-operative minor respiratory insults leading to development of negative pressure pulmonary oedema are still reported in 8% surgical patients undergoing nasal surgery (3). Author suggest an alternative approach in patients who undergo nasal surgery for therapeutic and cosmetic indications. This approach will overcome issues associated with nasal obstruction, nasal packing and use of nasal splints. It also attenuates the sympathetic surge associated with extubation and other respiratory complications. Moreover, it prevents the mechanical pressure on nose and may favour better nasal surgical cosmetic outcome. Author suggest the use of Laryngeal Mask Airway (LMA) at the end of nasal surgeries (septoplasty, rhinoplasty, functional endoscopic sinus surgery and repair of nasal laceration) as a face mask. Once the surgery ends, the effect of muscle relaxant is reversed while maintaining anaesthesia MAC at a deeper level (Isoflurane MAC 1.2 or Sevoflurane MAC 1.8 in 100% oxygen) and applying a 15-degree head down tilt. This is followed by the removal of throat pack and suctioning of oral cavity. Next step is to remove endotracheal tube from patient’s trachea followed by insertion of an appropriately sized oropharyngeal (Guedel) airway (Fig-Ia). Last step is to place an LMA over the patient’s lips and hold with both hands (Fig-Ib-Ic) to maintain an air tight seal. The patient breathes through the LMA and is allowed to wake up on the operating table. Positive pressure ventilation can also be applied if patient holds his breath or goes into laryngospasm without forcing any pressure over the nose. This approach avoids the direct mechanical pressure on operated nose. We have used this technique in our patients, and it was found useful approach.